Signaling about norms: socialization under strategic uncertainty - Adriani, Fabrizio; Sonderegger, Silvia (Wiley, 2016)
We consider a signaling model where adults possess information about the dominant social norm. Children want to conform to whatever norm is dominant but, lacking accurate information, take the observed behavior of their parent as representative. We show that this causes a signaling distortion in adult behavior, even in the absence of conflicts of interest. Parents adopt attitudes that encourage their children to behave in a socially safe way, i.e. the way that would be optimal under maximum uncertainty about the prevailing social norm. We discuss applications to sexual attitudes, collective reputation, and trust.